Vanillic acid combats Vibrio alginolyticus by cell membrane damage and biofilm reduction. Issue 11 (26th July 2021) - Liu, Huan; Xiao, Miao; Zuo, Jing; He, Xiaoxian; Lu, Ping; Li, Yingyu; Zhao, Yanni; Xia, Fei
Abstract: Antibiotics are the most powerful weapon against bacterial infectious diseases in aquaculture. However, the indiscriminate usage of antibiotics often culminates in the emerging development of antibiotic‐resistant bacteria, making it imperative to search for novel types of antimicrobial agents. This study investigated the antibacterial and antivirulence effects of vanillic acid (VA) against the fish pathogen, Vibrio alginolyticus . We showed that VA had a good anti‐ Vibrio activity with minimal inhibitory concentration (MIC) of 1.0 mg/ml. In addition, VA wielded its antibacterial action in a dose‐/time‐dependent manner by causing cell membrane damage and increasing membrane permeability, which is evidenced by increasing the conductivity and malondialdehyde content in the treated cell cultures and the scanning electron microscopy images. Furthermore, VA significantly reduced the biofilm‐forming capability, mobility and exotoxin production (protease and exopolysaccharide) and downregulation of the expression of biofilm‐ and virulence‐associated genes ( sypG, fliS, fliK, lafA, lafK, asp and luxR ) was seen in the V. alginolyticus that exposed to VA at subinhibitory concentrations. Overall, our findings suggested that VA may be of interest for treating V. alginolyticus ‐associated infections in aquaculture.